Comparing MCDM Methods for Assessing the Lecturer Performance Index at Dipa Makassar University - Suryani, Suryani; Patasik, Madyana; Zeannyfer, Stiffany Lourens; Syahputri, Andhiny Nurakzhany (Brilliance: Research of Artificial Intelligence, 2024)
Assessing or evaluating the Lecturer's Performance, presented through the Lecturer Performance Index, is a crucial element in the university system that impacts the quality of The University's Three Main Purposes, which include teaching, research, and community service. To ensure objective and accurate evaluations, methods that can accommodate various relevant criteria are needed. One increasingly popular approach is the Multi-Criteria Decision Making (MCDM) method, which allows for evaluating and comparing alternatives based on multiple criteria. This research compares several MCDM methods, namely Weighted Product (WP), Simple Additive Weighting (SAW), and Multi-Objective Optimization by Ratio Analysis (MOORA), used to assess the lecturer's performance at Dipa University Makassar. The WP method can handle criteria with different units, SAW is simpler and easier to apply, while MOORA offers a more comprehensive analysis. This study also identifies challenges in assessing the lecturer's performance, such as the influence of students' subjective evaluations that may lead to bias, as well as the addition of several of the lecturer's performance evaluation criteria such as teaching innovation, student mentoring, international and national journal publications, internal publications, and book publications. Additionally, self-development criteria based on academic fields are considered. The findings of this research are expected to provide insights into effective MCDM methods for the lecturer's performance evaluation and offer recommendations for educational institutions to choose the appropriate and transparent evaluation method. By using MCDM, the objectivity and accuracy of the lecturer's performance evaluations can be improved, biases can be reduced, and contributions can be made toward developing more fair and systematic evaluation standards.